Correlation between Enforcement of Environmental Law and Sustainable Development Goals in the Era of Society 5.0 - Purnaningtyas, Maria Ulfa Desvita (Universitas Negeri Semarang, 2023)
Development is the goal of advancing the growth of the Indonesian nation. Development must be based on the principles of sustainable development based on environmental principles. Sustainable development goals. However, implementation development is sometimes a bit slower in the era of society 5.0. By ignoring environmental aspects, the role of environmental criminal law is the legal basis for enforcing the authority exercised on the environment and the basis for criminal prosecution. This paper aims to analyze the correlation between environmental law enforcement and Sustainable development goals in the era of society 5.0. in this case the author uses a qualitative approach, with the data collection technique used is literature study. The results of this study the authors found that the pillars of the SDGs for the realization of environmentally sound development must be supported by political, legal and bureaucratic institutions in realizing equitable development and law enforcement in the era of society 5.0. Law enforcement based on Law 32 of 2009 concerning Environmental Protection and Management which is the result of several changes to the previous law, seems to have been able to provide fair law enforcement to the community and the environment in the era of society 5.0.